In vitro effects of aqueous extract from Artocarpus takoocha Roxb on tegumental surface of Haplorchis taichui. - Chalobol Wongsawad (2018)
The tegumental surface of the adult intestinal fluke, Haplorchis taichui, after in vitro incubation in Tyrode's solution containing 25, 50, 75 and 100% of aqueous extract of Artocarpus takoocha for 1, 6, 12 and 24 hours, was monitored by Scanning Electron Microscopy (SEM). The effect on worm motility was studied in contemporizing period. The adult worms stopped their motility immediately after being incubated with 25, 50, 75 and 100% of aqueous extract of A. takoocha. Observed under a light microscope, most worms showed bubbling from the oral sucker, ventral sucker and excretory pore. After exposure to the solution, SEM observation showed large blebs protruding from the oral sucker, ventral sucker and excretory pore. The surface damage was composed of numerous small blebs, followed later by the disruption of tegument. The severity of damage increased due to the increasing of aqueous extract of A. takoocha and incubation periods.